Travel Narratives in Rabbinic Literature Voyages to Imaginary Realms. - Grossmark, Tziona (Lewiston : Edwin Mellen Press, 2010)
As a literary genre travelers' stories have grown out of oral traditions. These traditions flourished along the trade routes of the ancient world. Indeed the roads around the Mediterranean basin were busy with traffic during the Roman and Byzantine periods. This anthology of twenty-one travelers' tales examines the Talmudic tales as an inter-cultural phenomenon.
Appendix 7 -- The Hebrew TextAppendix 8 -- A comparison of b.B. Bat. 74a and b. Ber. 3a; Appendix 9 -- A comparison of tales nos. 18-19; Bibliography; Indices; Index of Passages from Rabbinical Literature; Index of Hebrew and Aramaic Words; Index of Sages; General Index.
Description based on print version record.
Keywords: Biography in rabbinical literature; Rabbinical literature -- History and criticism; Rabbinical literature; Biography in rabbinical literature; Rabbinical literature -- History and criticism; RELIGION / Judaism / Talmud; Electronic books